Cooperativism in a Dirigiste State: SEKE and the Reconstruction of Greece’s Tobacco Sector (1947–1967) - Carmona-Zabala, Juan (John Hopkins University Press, 2023)
The Co-operative Union of Tobacco Producers of Greece (SEKE) made a series of key contributions to the reconstruction, and development, of Greek tobacco production and exports in the postwar period. Its strategies allowed tobacco growers to retain a larger part of the value that they produced. A historical analysis of SEKE’s emergence and early trajectory allows for a more complex narrative of the postwar economic reconstruction to emerge, in which we can appreciate the role of sub-state actors more clearly appreciated than has been the case thus far. By influencing the institutional framework regulating the tobacco sector, opening up new export markets and investing in human capital, SEKE partially actualized the agrarian political program of the interwar period. As a large trading firm owned by agricultural cooperatives, SEKE’s history forces us to revise the limited, often cynical view of Greek agrarian cooperativism as a mere mechanism for the enforcement of redistributive state policy, and the management of credit from the Agricultural Bank.
Política de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/8591#journalPolicy
Keywords: Tabaco - Cultivo - Grecia; Agricultura - Innovaciones tecnológicas; Agricultura - Grecia - 19..; Global production networks; Tobacco; Greece; Upgrading; Cooperatives; Rural history; Agriculture